Turizm Farkındalık Ölçeği Geçerlik ve Güvenirlik Çalışması. - Yakın, Fadime; Çukur, Hasan (Electronic Turkish Studies)
In order to develop and emphasize tourism in a region and to increase the income earned from this sector, the role and awareness of individuals living in that region in tourism should be increased. In this context, it is important to determine the tourism awareness of individuals/students about the place where they live. Especially secondary school students will be the individuals who will play an active role in this sector in the future, plan tourism and generate new ideas on this subject. Because these students are the ones who will move on to university after the secondary education period or who will choose their professions after this period. Therefore, this study aims to develop a valid and reliable tourism awareness scale for secondary school students. Cross-sectional survey model, one of the quantitative research methods, was used in the study. The research population of the study consists of secondary school students studying in Uşak. Convenient sampling method was used in sample selection. A total of 920 students studying in the first semester of the 2021-2022 academic year participated in the study. For factor analysis, KMO (,889) and Barlett Sphericity tests (2179,111) (p ≤ .00) were performed and the values were found appropriate. Principal component analysis (PCA) was applied in the factor elicitation process. Confirmatory factor analysis (CFA) was conducted to determine the fit of the resulting model with the data. IBM SPSS and AMOS 24 programs were used to analyze the data. As a result of the analysis, a 4-dimensional scale consisting of 18 items was obtained. The dimensions of the scale were named as “Awareness towards Nature Tourism”, “Awareness towards Cultural Tourism Places”, “Awareness towards Cultural Tourism Activities” and “Awareness towards Sports Tourism”. The total variance of the scale was 56,070% and the overall Cronbach's alpha coefficient was,857. As a result of the study, a valid and reliable scale that can be used to determine the tourism awareness of individuals/students was obtained.